Reallocation of organic functions on the example of domestic subsidiary - a case study = Realokacja funkcji organicznych na przykładzie krajowej spółki zależnej - studium przypadku - Sobotkiewicz, Dariusz (Zielona Góra: Faculty of Economics and Management Press)
This elaboration discusses organic functions problem with respect to changes of their distribution based on an example of a domestic subsidiary that is a part of a holding. The theoretical part shows that the evolution of organizational structure and the change in the perception of the role of subsidiaries in the entire holding affect the reallocation of organic functions.
Keywords: spółka zależna; jednostka zależna; jednostka nadrzędna; funkcje organiczne; subfunkcje; rozmieszczenie funkcji; parent institution; subsidiary; organic functions; subfunctions; distribution of functions